Telemedicine in Dermatology - Soyer, H. Peter; Binder, Michael; Smith, Anthony C.; Wurm, Elisabeth M.T.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
Written by leading teledermatologists and telemedicine experts, this hands-on guide addresses the practical needs of the many emerging teledermatology services worldwide. It: •          Covers the medical and technical prerequisites for such services as well as the photographic imaging essentials •          Illustrates the performance of teledermatology by way of clinical examples •          Discusses teledermatology in underdeveloped countries •          Presents specialized methods of teledermatology •          Explores the impact of telemedicine on the doctor-patient relationship •          Explains the advantages that accrue from improving access to expert knowledge •          Pays careful attention to quality assurance, legal assumptions, economic aspects, and the future horizons of such health care services. •          Includes a comprehensive appendix comprising education and training opportunities, sample protocols, consent forms, information sheets, references, and relevant web links   This guide is a must-have for all those who treat patients with inflammatory and neoplastic skin diseases.
Introduction to Teledermatology -- Historical Review -- Medical Prerequisites -- Technical Prerequisites -- Photographic Imaging Essentials -- Performance of Teledermatology including Clinical Examples -- Teledermatology in Underdeveloping Countries -- Special Methods of Teledermatology -- Teledermatology and Reflectance Confocal Microscopy Quality Assurance -- Legal Assumptions -- Economic Aspects and Cost-effectiveness -- Future Horizons -- APPENDIX: Education and Training Opportunities -- Quality Certificate Teledermatology -- Sample Protocol, Consent Form and Information Sheet -- References and Relevant Web links -- Glossary -- Subject Index.
Keywords: Dermatology; Oncology .; Plastic surgery; Pediatrics; Internal medicine; Dermatology; Oncology; Plastic Surgery; Pediatrics; Internal Medicine